2019
DOI: 10.3892/ol.2019.11184
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA MALAT1 activates autophagy and promotes cell proliferation by downregulating microRNA‑204 expression in gastric cancer

Abstract: Gastric cancer (GC) is one of the major diseases that threaten human health. Although the development of novel drugs has significantly improved the efficacy of GC chemotherapy, the 5-year survival rate of patients with GC remains unsatisfactory. In the present study, the role and mechanism of the long non-coding RNA (lncRNA) metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) in GC proliferation was investigated. Clinical specimens and cancer cells were analyzed by western blotting or immunofluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 50 publications
0
38
0
Order By: Relevance
“…[12][13][14] An increasing number of studies have shown that numerous lncRNAs are abnormally expressed in GC. [15][16][17] Notably, there is increasing evidence supporting a close relationship between lncRNA dysregulation and malignant characteristics in GC. 18,19 MicroRNAs (miRNAs, miRs) are classified as singlestranded noncoding short RNAs approximately 19-25 nucleotides in length.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] An increasing number of studies have shown that numerous lncRNAs are abnormally expressed in GC. [15][16][17] Notably, there is increasing evidence supporting a close relationship between lncRNA dysregulation and malignant characteristics in GC. 18,19 MicroRNAs (miRNAs, miRs) are classified as singlestranded noncoding short RNAs approximately 19-25 nucleotides in length.…”
Section: Introductionmentioning
confidence: 99%
“…In acute myeloid leukemia, lncRNA UCA1 promotes autophagy by targeting miR-96-5p ( 35 ). lncRNA MALAT1 activates autophagy and promotes the cell proliferation by downregulating the miRNA-204 expression in gastric cancer ( 36 ). However, to-date, there has been no systematic and comprehensive analysis of autophagy-related lncRNA in BC.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, some lncRNAs were de ned as protective factors while others were risk factors [25,[41][42][43][44]. Furthermore, several studies have proved that lncRNAs participated in the progression, especially malignant progression of GC through regulating autophagy-related mRNAs [24][25][26][27][28][29]45].…”
Section: Discussionmentioning
confidence: 99%
“…Pieces of evidence showed that lncRNA is vital for the occurrence, prognosis, and chemoresistance of GC by regulating autophagy-related mRNA [24][25][26]. Some studies have demonstrated that silencing of LINC01419 and CCAT2 promotes autophagy through constraining the PI3K/Akt1/mTOR pathway thus inhibiting the invasion and migration of GC cells [27,28]; Another study also revealed that autophagy was associated with the proliferation of GC cells, partially due to the MALAT1 promoted by downregulating miR-204 [29]. However, most of these experiments only explored the role of one or a few lncRNAs in the autophagy of GC, and could not fully explain the relevant mechanisms.…”
Section: Introductionmentioning
confidence: 99%